Collaboration as a Driving Factor for Hit Song Classification - Silva, Mariana O.; Oliveira, Gabriel P.; Seufitelli, Danilo B.; Lacerda, Anisio; Moro, Mirella M. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2022)
The Web has transformed many services and products, including the way we consume music. In a currently streaming-oriented era,predicting hit songs is a major open issue for the music industry.Indeed, there are many efforts in finding the driving factors that shape the success of songs. Yet another feature that may improve such efforts is artistic collaboration, as it allows the songs to reach a wider audience. Therefore, we propose a multi-perspective approach that includes collaboration between artists as a factor for hit song prediction. Specifically, by combining online data from Billboard and Spotify, we model the issue as a binary classification task by using different model variants. Our results show that relying only on music-related features is not enough, whereas models that also consider collaboration features produce better results.